Hybrider le climat et les luttes - Berthier, Aurélien; Mourin, Barbara (Agir par la culture, 2018)
Le concept d’intersectionnalité définit les points de rencontre entre des luttes contre les dominations liées à la classe sociale, à la racisation ou au genre. Il a permis réflexions et nouveaux champs de bataille féconds. Activistes et intellectuel·les proposent de continuer à multiplier les hybridations entre ces combats sociaux, culturels et politiques avec les luttes environnementales et climatiques. Prenant... View Article
Keywords: approches et analyses; capitalisme; environnement; intersectionnalité; justice sociale; militance; patriarcat; projet charge mentale; ressource en ligne; systèmes d'oppressions; thématiques; écoféminisme

Emma - Emma (Emma, 2017)
Politique, trucs pour réfléchir et intermèdes ludiques
Keywords: 2000 à aujourd'hui; anticapitalisme; approches et analyses; bande-dessinée; charge mentale; charge émotionnelle; environnement; humour; patriarcat; projet charge mentale; périodes historiques; racisme; ressource en ligne; sexisme; sexualité; systèmes d'oppressions; thématiques; travail; travail invisible; violences; violences policières

Visual representation of gender in flood coverage of Pakistani print media - Ali, Zarqa S. (Weather and Climate Extremes, 2014)
This paper studies gender representation in the visual coverage of the 2010 floods in Pakistan. The data were collected from flood visuals published in the most circulated mainstream English newspapers in Pakistan, Dawn and The News. This study analyses how gender has been framed in the flood visuals. It is argued that visual representation of gender reinforces the gender stereotypes and cultural norms of Pakistani society. The gender-oriented flood coverage in both newspapers frequently seemed to take a reductionist approach while confining the representation of women to gender, and gender-specific roles. Though the gender-sensitive coverage displayed has been typical, showing women as helpless victims of flood, it has aroused sentiments of sympathy among readers and donors, inspiring them to give immediate moral and material help to the affected people. This agenda set by media might be to exploit the politics of sympathy but it has the effect of endorsing gender stereotypes.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; cinéma; communication; discipline; environnement; inondations; médias; pakistan; patriarcat; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; stéréotypes de genre; systèmes d'oppressions; thématiques